Effect of process-based strategies on anaerobic digestion of 3D-printing-derived polylactic acid: biogas production and mechanistic interpretation - Davide Giandomenico; Alessandro Gottuso; Rocco Rubino; Alberto Ferraro; Luca Fambri; Francesco Parrino; Raffaele Morello; Francesco Bianco; Gennaro Trancone; Umberto Fratino; Danilo Spasiano (Biomass and Bioenergy, 2026)

Habitat Selection and Population Density of Diurnal and Nocturnal Lemurs in the Anjozorobe-Angavo Protected Area, Madagascar - Giulia Sassoli; Aurelia Sebastiani; Davide Mirante; Hanitriniaina Raharinirina; Rojotiana N. Rakotoarisoa; N. M. Koloina Rakotoarivelo; Fanomezantsoa L. Ravololoniaina; H. Domohina S. Randrianarisoa; Gabriele Ferraro; S. Jacques Rakotondranary; Timothy M. Eppley; Luca Santini (International Journal of Primatology, 2026)
Primates are among the most threatened mammals globally owing to rapid habitat loss and intense hunting pressure. Among these, lemurs are the taxon with the highest number of species at risk of extinction. Although many lemur species have been surveyed extensively across Madagascar, some taxa and protected areas remain understudied. The Anjozorobe-Angavo Protected Area, a rainforest landscape in the highlands of central-eastern Madagascar, has received relatively little ecological attention and continues to experience deforestation. This study was designed to estimate the population density and habitat selection of diurnal and nocturnal lemur species within La Mananara, a privately owned forest within Anjozorobe-Angavo. We conducted line-transect surveys over a 3-month period, between October and December 2024, and applied distance sampling to estimate species abundance. We also collected data on species detection locations and established vegetation plots to characterize habitat structure and evaluate species-specific habitat associations through resource selection functions. We recorded four diurnal and six nocturnal lemur species. Nocturnal species exhibited higher estimated densities and were more frequently encountered in areas with human activity, whereas diurnal species were less abundant and generally showed stronger associations with areas characterized by greater canopy cover and lower anthropogenic disturbance. Our findings underscore the conservation importance of primary forest protection, while also demonstrating the role of edge habitat and human-modified habitats for certain nocturnal taxa. These density estimates represent a quantitative assessment for this area, helping to inform the management of La Mananara, and contributing to broader conservation assessments of lemur populations within this under-characterized protected landscape.

Highly sensitive detection of different aggregation stages of Aβ1-42 -amyloid peptide in urine-like samples by auto-fluorescence - Concetta Di Natale; Sara La Manna; Stefania Carbone; Sara Coppola; Veronica Vespini; Volodymyr Tkachenko; Daniele Tammaro; Simone Russo; Giuseppe Vitiello; Giuseppina Luciani; Daniela Marasco; Pier Luca Maffettone; et al. (Analytica Chimica Acta, 2025)

AgrOptim: A novel multi-objective simulation optimization framework for extensive cropping systems - Felipe Ghersa; Lucas A. Figarola; Rodrigo Castro; Diego O. Ferraro (Computers and Electronics in Agriculture, 2024)

Characterisation of microbial communities and quantification of antibiotic resistance genes in Italian wastewater treatment plants using 16S rRNA sequencing and digital PCR - Giusy Bonanno Ferraro; Carmelo Bonomo; David Brandtner; Pamela Mancini; Carolina Veneri; Rossella Briancesco; Anna Maria Coccia; Luca Lucentini; Elisabetta Suffredini; Dafne Bongiorno; Nicolò Musso; Stefania Stefani; et al. (Science of The Total Environment, 2024)

Signature of paraoxonases in the altered redox homeostasis in Alzheimer's disease - Sarah Beggiato; Francesca Ferrara; Arianna Romani; Tommaso Cassano; Alessandro Trentini; Giuseppe Valacchi; Carlo Cervellati; Luca Ferraro (Chemico-Biological Interactions, 2024)

Wastewater-based Epidemiology and SARS-CoV-2: Variant Trends in the Apulia Region (Southern Italy) and Effect of Some Environmental Parameters - Francesco Triggiano; Osvalda De Giglio; Francesca Apollonio; Silvia Brigida; Fabrizio Fasano; Pamela Mancini; Giusy Bonanno Ferraro; Carolina Veneri; Giuseppina La Rosa; Elisabetta Suffredini; Luca Lucentini; Nicola Ungaro; et al. (Food and Environmental Virology, 2023)
During the COVID-19 pandemic, wastewater monitoring has been used to monitor the levels of SARS-CoV-2 RNA entering the sewerage system. In Italy, the Istituto Superiore di Sanità coordinated the SARI project (Sorveglianza Ambientale Reflue in Italia) to detect SARS-CoV-2 and its variants. In this study, the concentration of SARS-CoV-2 and its variants in raw wastewater against COVID-19 cases was evaluated together with the effect of temperature and precipitation on virus spread. We validated a predictive model, proposed by De Giglio et al., 2021, to establish the number of COVID-19 cases/100,000 inhabitants. A receiver operating characteristic curve model was applied to predict the number of COVID-19 cases and Poisson regression was applied to study the effect of temperature and rainfall on viral load. In Apulia, from October 2021 to December 2022, we analyzed 1041 samples, of which 985 (94.6%) tested positive for SARS-CoV-2. Median atmospheric temperature was inversely proportional to viral load in wastewater; no correlation was found with precipitation. The predictive model confirmed that at least 11 cases/100,000 inhabitants would occur in the 15 days following the detection of the virus in wastewater. Environmental surveillance of SARS-CoV-2 can be used to map the virus and its variants.

Improving in vivo oral bioavailability of a poorly soluble drug: a case study on polymeric versus lipid nanoparticles - Giovanna Rassu; Antonella Obinu; Carla Serri; Sandra Piras; Antonio Carta; Luca Ferraro; Elisabetta Gavini; Paolo Giunchedi; Alessandro Dalpiaz (Drug Delivery and Translational Research, 2023)

Spinocerebellar Ataxia Type 1: One-Year Longitudinal Study to Identify Clinical and MRI Measures of Disease Progression in Patients and Presymptomatic Carriers - Anna Nigri; Lidia Sarro; Alessia Mongelli; Anna Castaldo; Luca Porcu; Chiara Pinardi; Marina Grisoli; Stefania Ferraro; Laura Canafoglia; Elisa Visani; Maria Grazia Bruzzone; Lorenzo Nanetti; et al. (The Cerebellum, 2022)

Modulating Long Term Memory at Late-Encoding Phase: An rTMS Study - Giuseppe Giglia; Giuditta Gambino; Luca Cuffaro; Fabio Aleo; Pierangelo Sardo; Giuseppe Ferraro; Valeria Blandino; Filippo Brighina; Massimo Gangitano; Tommaso Piccoli (Brain Topography, 2021)

On Caretta caretta ’s shell: first spatial analysis of micro- and macro-epibionts on the Mediterranean loggerhead sea turtle carapace - Monica Francesca Blasi; Alice Rotini; Tiziano Bacci; Monica Targusi; Giusy Bonanno Ferraro; Luca Vecchioni; Rosa Alduina; Luciana Migliore (Marine Biology Research, 2021)

Acute Cocaine Enhances Dopamine D2R Recognition and Signaling and Counteracts D2R Internalization in Sigma1R-D2R Heteroreceptor Complexes - Dasiel O. Borroto-Escuela; Manuel Narváez; Wilber Romero-Fernández; Luca Pinton; Karolina Wydra; Malgorzata Filip; Sarah Beggiato; Sergio Tanganelli; Luca Ferraro; Kjell Fuxe (Molecular Neurobiology, 2019)

Astrocytic Mechanisms Involving Kynurenic Acid Control Δ9-Tetrahydrocannabinol-Induced Increases in Glutamate Release in Brain Reward-Processing Areas - Maria E. Secci; Paola Mascia; Claudia Sagheddu; Sarah Beggiato; Miriam Melis; Andrea C. Borelli; Maria C. Tomasini; Leigh V. Panlilio; Charles W. Schindler; Gianluigi Tanda; Sergi Ferré; Charles W. Bradberry; et al. (Molecular Neurobiology, 2019)

Facilitation and interference components in the joint Simon task - Luca Ferraro; Cristina Iani; Michele Mariani; Nadia Milanese; Sandro Rubichi (Experimental Brain Research, 2011)